Migration and Remittances : Recent Developments and Outlook - Transit Migration - World Bank Group (World Bank, Washington, DC, 2018)
This Migration and Development Brief reports global trends in migration and remittance flows, as well as developments related to the Global Compact on Migration (GCM), and the Sustainable Development Goal (SDG) indicators for volume of remittances as percentage of gross domestic product (GDP) (SDG indicator 17.3.2), reducing remittance costs (SDG indicator 10.c.1) and recruitment costs (SDG indicator 10.7.1). This Brief has a special focus on transit migration.